KEY ELEMENTS: GENDER, PEMBANGUNAN, DAN KELOMPOK PEREMPUAN - Putra, Ari; Safitri, Ani (Program Studi Pendidikan Luar Sekolah, 2024)
Gender and development are intricately linked concepts within the global development framework, with the role of women's groups garnering increasing recognition for their substantial contributions across various sectors. Despite this recognition, women's groups encounter numerous challenges in their pursuit of gender equality and sustainable development. This literature review aims to delve into the nuances of gender and development through the lens of women's groups, shedding light on key issues and contemporary research trends in this domain. Employing a rigorous literature review methodology, this study draws on a range of scholarly articles, books, and reports sourced from reputable online databases. The findings underscore the vulnerability of women's groups, highlighting prevalent inequalities in their access to resources and opportunities. Central themes in current research include economic empowerment and political participation, both crucial for advancing gender equality. Moreover, emerging research trends emphasize the necessity of a comprehensive, integrated approach to comprehensively understand the challenges faced by women's groups. Furthermore, the integration of gender perspectives in development policy formulation is increasingly recognized as pivotal for fostering inclusive and sustainable development. This review underscores the imperative for collaborative efforts among diverse stakeholders to advance gender equality and inclusive development for women's groups.